Legal Philosophy’s Role in Human Rights and Fiscal Governance: Indonesia and the Philippines Comparative Insights - Aneta, Yanti; Aneta, Asna; Tohopi, Rustam; Hulinggi, Pebriyanto A.; Tee-Anastacio, Princess Alyssa D. (Universitas Negeri Surabaya, 2025)
This article addresses the critical gap in the insufficient integration of legal-philosophical principles—such as justice, equity, and the rule of law—into local fiscal policy frameworks. This research adopts a normative-juridical method with a comparative and conceptual approach. Data were analyzed through classical and contemporary legal-philosophical perspectives to evaluate the extent to which legal norms are either upheld or neglected in budgeting processes and fiscal governance. The findings reveal that Indonesia’s legal framework emphasizes decentralization and participatory budgeting but lacks mechanisms to ensure rights-based fiscal priorities. Conversely, the Philippines exhibits stronger civil society engagement in local fiscal issues but faces challenges of legal fragmentation and weak enforcement. Both countries demonstrate a limited philosophical foundation in fiscal policymaking, which undermines the realization of social and economic rights.This study concludes that embedding legal philosophy into local fiscal governance is essential for advancing the substantive fulfillment of human rights. The article recommends the institutionalization of rights-based budgeting principles, enhanced legal education for local officials, and stronger normative alignment between decentralization laws and human rights obligations.